Trends in Game-Based E-Module Development for Elementary Science and Social Studies Education: A Bibliometric Review (2020-2025) - Niken Nastiti; Nuni Widiarti; Bambang Subali (Papanda Publisher, 2026)
This study aimed This study aimed to analyze trends and directions in Game-Based Learning (GBL)-based e-module research in Natural and Social Sciences (IPAS) teaching at the elementary school level from 2020 to 2025. The study employed a Systematic Literature Review (SLR) with a bibliographic approach guided by the PRISMA framework. Data were collected from scientific databases and analyzed using bibliometric visualization and content analysis techniques. Of 1,277 initially identified articles, 490 met the eligibility criteria, with 34 articles selected for in-depth bibliometric and content analysis. The findings indicate a steady growth in publications related to GBL-based e-modules, with the highest increase observed in 2024. Research focus has shifted from simple media digitization toward the design of interactive e-modules that promote motivation, collaboration, and 21st-century competencies. The reviewed studies highlight that integrating game elements in e-modules enhances students’ engagement, scientific understanding, and learning outcomes. Furthermore, emerging trends point to the integration of smart technologies such as artificial intelligence and augmented reality, as well as project-based learning models that emphasize contextual and student-centered experiences. These findings affirm that GBL-based e-modules hold strong potential as a strategic medium for supporting the implementation of the Merdeka Curriculum, fostering adaptive, reflective, and sustainable learning environments in elementary schools.